Penggunaan Metode Ruas Jari dalam Pembelajaran Isim Dhamir - Rahmi, Aulia; Chairullah, Chairullah (Serambi Tarbawi, 2024)
One of the language rules in Arabic is isim dhamir. Isim dhamir is a pronoun that indicates a person. In Arabic dhamir there are three dhamir muttasil, munfashil and mustatir. The dhamir that the author discusses here is dhamir rafa' munfashil which is part of dhamir munfashil. There are fourteen dhamir rafa' munfashil in all, and it is these dhamirs that are used in Arabic conversation. Because the number is so large, it is different from Indonesian, which only has six pronouns, making it very difficult for students, especially those who are first introduced to Arabic, to understand and differentiate between the dhamir contents. Therefore, the author offers a method to make it easier for students to master isim dhamir, namely the finger joint method. The finger joint method is a method that uses each joint on the finger to understand the meaning of each dhamir term from dhamir "huwa" to dhamir "nahnu".